The impact of extrinsic rewards toward employee's job performance at TM, Melaka / Athirah Ahmad Daniar...[et al] - Ahmad Daniar, Athirah (Faculty of Business and Management, 2012)
This study was conducted to explain the impact of extrinsic rewards toward employee's job performance. The study was carried out at TM, Melaka. The study involved 123 respondents with employee categories which include top level management, middl e management and lower level management. The researcher study this topic because usually the organizations only focus on extrinsic rewards compared with the intrinsic rewards. Moreover, the research objective in this study indicates to determine the level of the employee's job performance, to identify the impact of extrinsic reward toward employee' s job performance, and to identify the most influence elements of extrinsic rewards that give impact toward employee 's job performance. Furthermore , employees from a wider range and different levels of employment may present different perceptive of the findings.